2018
DOI: 10.1186/s13063-018-2660-1
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Intervention Accentuating Diet and Enhancing Metabolism (DIADEM-I): a randomised controlled trial to examine the impact of an intensive lifestyle intervention consisting of a low-energy diet and physical activity on body weight and metabolism in early type 2 diabetes mellitus: study protocol for a randomized controlled trial

Abstract: BackgroundType 2 diabetes mellitus (T2DM) and obesity are syndemic and will have a significant impact on affected individuals and healthcare services worldwide. Evidence shows that T2DM remission can be achieved with significant weight loss in those who are younger with early diabetes and requiring fewer medications for glycaemic control. DIADEM-I aims to examine the impact of an intensive lifestyle intervention (ILI) using a low-energy diet (LED) meal replacement approach combined with physical activity in yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Also, multidisciplinary approaches with structured interventions combining dietary interventions with exercise and/or behavioural support were rarely used. The results of RCTs using multidisciplinary approaches and evidence based clinical expertise will provide key information about the applicability and acceptability of lifestyle interventions for weight loss in this region 42 …”
Section: Discussionmentioning
confidence: 99%
“…Also, multidisciplinary approaches with structured interventions combining dietary interventions with exercise and/or behavioural support were rarely used. The results of RCTs using multidisciplinary approaches and evidence based clinical expertise will provide key information about the applicability and acceptability of lifestyle interventions for weight loss in this region 42 …”
Section: Discussionmentioning
confidence: 99%
“…T2D and excess adiposity are linked with one another. Recent evidence shows that weight reduction through medical interventions or bariatric surgery can cause remission in T2D in young people and in those with recent onset of disease [78]. The Diabetes Intervention Accentuating Diet and Enhancing Metabolism (DIA-DEM-I) study is a current, non-blinded, pragmatic, randomized, controlled, parallel-group trial.…”
Section: Combination Of Very-low-calorie Diet and Exercise In Improving The Biomarkers Of Type-2 Diabetesmentioning
confidence: 99%
“…The Diabetes Intervention Accentuating Diet and Enhancing Metabolism (DIA-DEM-I) study is a current, non-blinded, pragmatic, randomized, controlled, parallel-group trial. It includes 138 subjects, younger adults with T2D, in the early stage of diabetes (≤ 3 year duration) who have undergone intensive lifestyle intervention changes (i.e., 800 kcal/day intake and 150 min/week exercise for 12 weeks) and results are hoped to identify a path to reversal of T2D [78]. Recent evidence has also reported that low-calorie diet and lifestyle interventions resulted in a significant improvement and T2D remission [79].…”
Section: Combination Of Very-low-calorie Diet and Exercise In Improving The Biomarkers Of Type-2 Diabetesmentioning
confidence: 99%
“…The sample size is based on a clinically relevant difference in HbA1c of 0.5% (5.5mmol/mol) SD 1% (11mmol/mol) between the intervention and the standard care arms (25). To achieve an 80% power and a signi cance level of <0.05, 64 participants are required in each arm.…”
Section: Sample Size {14}mentioning
confidence: 99%